Development of ICT in Five Private University Libraries of West Bengal in New Town Area: A Study - Paul, Prasenjit; Maity, Arabinda (Journal of Advanced Research in Library and Information Science; Vol 9 No 1 (2022): Journal of Advanced Research in Library and Information Science, 2023)
This present study has been conducted to analyze the ICT application in library automation of five private Universities situated in the New Town area in West Bengal. To finish the investigation, a well-structured questionnaire was created. The study’s conclusions provide important information on the library’s ICT infrastructure and information services of five private Universities situated in the New Town area. It has been tried to find out different sections where automation has been completed and the sections where automation is under progress. The article tried to reveal the budget allocation, staff pattern, library use, software, hardware system, etc. Based on content analysis square measure provided at the end of the paper for the development and implementation of the automation and e-awareness program. Based on the findings, it was noted that the library does not have enough internet nodes or bandwidth, hardware, or software resources. The university’s campus LAN has not yet fully expanded to take use of the advantages of the digital information environment. Finally, it highlighted the problems associated with ICT applications and suggests some probable solutions at the end. How to cite this article:  Paul P, Maity A. Development of ICT in Five Private University Libraries of West Bengal in New Town area: A Study. J Adv Res Lib Inform Sci 2022; 9(1): 19-27. DOI: https://.doi.org/10.24321/2395.2288.202205